2018
DOI: 10.1016/j.dnarep.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of oxidized base repair-initiating NEIL1 DNA glycosylase required for chromatin-bound repair complex formation in the human genome increases cellular resistance to oxidative stress

Abstract: Posttranslational modifications of DNA repair proteins have been linked to their function. However, it is not clear if posttranslational acetylation affects subcellular localization of these enzymes. Here, we show that the human DNA glycosylase NEIL1, which is involved in repair of both endo- and exogenously generated oxidized bases via the base excision repair (BER) pathway, is acetylated by histone acetyltransferase p300. Acetylation occurs predominantly at Lys residues 296, 297 and 298 located in NEIL1's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…These analyses revealed deregulation of genes reported to be altered in previous CML investigations, such as RXFP1, 43 PIEZO2, 55 and CD26, 56 and in leukemia studies, such as CD69, 57 ST18, 58 and MUC4. 59 Expression analysis also suggested that DNA damage could be related to the downregulation of DNA-repair machinery genes and that dysregulation events in genes, including DNMT1, 60 SEPP1, 61 NEIL1, 62 and WT1, 63,64 may have contributed to the high occurrence of DNA damage-associated variants in our cohort. In addition, several immune checkpoint genes were found to be deregulated, suggesting an explanation for how CML cells evade immune-cell clearance.…”
Section: Discussionmentioning
confidence: 74%
“…These analyses revealed deregulation of genes reported to be altered in previous CML investigations, such as RXFP1, 43 PIEZO2, 55 and CD26, 56 and in leukemia studies, such as CD69, 57 ST18, 58 and MUC4. 59 Expression analysis also suggested that DNA damage could be related to the downregulation of DNA-repair machinery genes and that dysregulation events in genes, including DNMT1, 60 SEPP1, 61 NEIL1, 62 and WT1, 63,64 may have contributed to the high occurrence of DNA damage-associated variants in our cohort. In addition, several immune checkpoint genes were found to be deregulated, suggesting an explanation for how CML cells evade immune-cell clearance.…”
Section: Discussionmentioning
confidence: 74%
“…Because acetylation covalently modifies many proteins, it has strong chromatin-modifying potential in DNA repair, transcription and replication. Some evidence has suggested that histone deacetylase (HDAC) inhibitors exert neuroprotective effects against various insults and deficits in the central nervous system [28,29], and some protein acetylation can help cell survive and resist to oxidative stress [30].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…We speculated that to efficiently coordinate histone/CpG demethylation and repair of the demethylation-induced genome damage, the demethylases and BER/SSBR proteins colocalize in chromatin-bound preformed complexes. We extensively characterized chromatin-bound multiprotein complexes that contained BER/SSBR proteins, along with nonrepair proteins; furthermore, we showed that these complexes were competent in repairing the oxidized bases ( 33 36 ). Exposure to ROS increased the stability of these unique complexes, which were distinct for various BER subpathways ( 23 , 34 , 35 , 37 ).…”
Section: Resultsmentioning
confidence: 99%